CBSE Class 8CBSE
Share
Notifications

View all notifications

Reducing Equations to Simpler Form

Login
Create free account


      Forgot password?

notes

For example : `(6x + 1)/ 3 + 1 = (x - 3)/6`
Solution : Multiplying both sides of the equation by 6, 
`(6(6x + 1))/3 + 6 xx 1 = (6(x - 3))/6`
or 2 (6x + 1) + 6 = x – 3  
or 12x + 2 + 6 = x – 3            (opening the brackets ) 
or 12x + 8 = x – 3 
or 12x – x + 8 = – 3 
or 11x + 8 = – 3 
or 11x = –3 – 8 
or 11x = –11 
or x = – 1
Check:  LHS

= `(6(-1) + 1) / 3 +1 = (-6+1)/3 + 1 = -5/3 + 3/3 = (-5+3)/3 = -2/3`

RHS = `((-1)-3) /6 = -4 / 6 = -2/3`

LHS = RHS. (as required)

S
View in app×